The significance of the Hungarian wheat production in relation to the common agricultural policy - Mizik Tamás (Review on agriculture and rural development, 2021)
Wheat is one of the most important domestic crops, as well as one of the most important cereals. It has a wide range of use, not only for making basic foods but it is also widely used for animal feeding. The market competitiveness of the production can be measured in different ways. The average yield is one of them, which fluctuates strongly from year to year, mostly driven by weather conditions. Besides, the use of proper seeds and fertilizer, especially nitrogen and potassium, is essential. On the sales side, the price determines the effectiveness of production. Of course, the impacts of the Common Agricultural Policy should not be ignored as direct payments contributed to the gross revenue of crop producers by 57.2% on average. The aim of the article is to present these elements between 2010 and 2020 and to formulate agricultural policy recommendations based on the results obtained. The production and export of higher value-added products, such as various durable foods, but at least seed or durum variety, should be a priority of the Hungarian agricultural policy. This could also stimulate the manufacturing industry, which would have a positive employment effect in addition to an even larger trade surplus. However, the tremendous, 30% price increase in 2021 may not encourage the different stakeholders of the supply chain for any changes.